Infant feeding, wheezing, and allergy: a prospective study. Issue 6 (June 1993) - Burr, M L; Limb, E S; Maguire, M J; Amarah, L; Eldridge, B A; Layzell, J C; Merrett, T G
Abstract : The determinants of wheezing and allergy were investigated in 453 children with a family history of allergic disease. A randomised controlled trial examined the effects of withholding cows' milk protein during the first three months of life and replacing cows' milk with soya milk. The children were followed up to the age of 7 years. Withholding cows' milk did not reduce the incidence of allergy or wheezing. Children who had ever been breast fed had a lower incidence of wheeze than those who had not (59% and 74% respectively). The effect persisted to age 7 years in the non-atopics only, the risk of wheeze being halved in the breast fed children after allowing for employment status, sex passive smoking, and overcrowding. Allergic disease was not associated with exposure to tobacco smoke, house dust mite antigen, or cats. Breast feeding may confer long term protection against respiratory infection.